Micromorphology and origin of an unusual bear fur-bearing deposit in Bàsura Cave (Toirano, NW Italy) - Rellini, Ivano; Firpo, Marco; Arobba, Daniele; Starnini, Elisabetta; Romano, Marco; Citton, Paolo; Salvador, Isabella; Negrino, Fabio; Avanzini, Marco; Zunino, Marta (Quaternary International)
The Bàsura Cave (Toirano, Savona, NW Italy) hosts important cave bear bone assemblages and a numerous and varied, tracks and traces record left by humans and other producers. An outstanding element of the analysed material is represented by fossil bear fur fragments, which were found in the inner deposits of the cave, and that, to date, are virtually unknown in the cave global record. After analysing and discussing micromorphological features of the inedited material, we integrate and interpret new radiocarbon data, along with taphonomic, sedimentological, geochemical and mineralogical evidences, with the aim of improving our understanding about the nature and chronology of the bear fur-bearing deposit. The bear fur fragments are included in a stratigraphic succession corresponding to a secondary deposit, formed after the dismantling, reworking and redeposition of a former bear-bearing deposit, as a result of short but intensive flooding events that most probably took place at the end of the Last Glacial Maximum. After sediments redeposition, important diagenetic changes have occurred and probably driven by guano deposits, whose pre-existence, in absence of record, is inferred from corrosion features, nutrient concentrations, mineral species identified (REE bearing hydroxyapatite), and claw traces left by bats on the cave ceiling and walls. Diagenetic imprint derived by guano deposits caused mineralization of bear fur fragments by replacement with apatite, which faithfully copied the form and structure of hairs but also of vegetal tissues, phytoliths and pollen found within them. Our study demonstrates for the first time that the bear fur is one of the main vectors in introducing botanical microremains into the interior of the “Old World” caves. Fil: Rellini, Ivano. Università degli Studi di Genova; Italia Fil: Firpo, Marco. Università degli Studi di Genova; Italia Fil: Arobba, Daniele. Museo Archeologico del Finale; Italia Fil: Starnini, Elisabetta. Università degli Studi di Pisa; Italia Fil: Romano, ...